Dexmedetomidine versus midazolam for gastrointestinal endoscopy: A meta‐analysis. Issue 1 (4th December 2014) - Nishizawa, Toshihiro; Suzuki, Hidekazu; Sagara, Seiji; Kanai, Takanori; Yahagi, Naohisa
<x xml:space="preserve">Abstract</x> Background and Aim Patients who undergo gastrointestinal endoscopy often require sedatives such as midazolam and the more recently developed alpha‐2 agonist, dexmedetomidine. To assess the efficacy and safety of dexmedetomidine sedation for gastrointestinal endoscopy, we conducted a systematic review and meta‐analysis of randomized controlled trials comparing dexmedetomidine with midazolam. Methods We searched PubMed, the Cochrane library, and the Igaku‐chuo‐zasshi database in order to identify randomized trials eligible for inclusion in our meta‐analysis. Data from the eligible studies were combined to calculate pooled odds ratios (OR) or weighted mean differences (WMD). Results We identified nine randomized trials from the database search. Compared to that of midazolam, the pooled OR for restlessness of dexmedetomidine was 0.078 (95% confidence interval [CI]: 0.013–0.453, P < 0.0001), and there was no significant heterogeneity among the trial results. Dexmedetomidine significantly increased Ramsay sedation score compared with midazolam (WMD: 0.401, 95% CI: 0.110–0.692, P = 0.0069), without significant heterogeneity. Compared with midazolam, the pooled OR for hypoxia, hypotension, and bradycardia with dexmedetomidine sedation were 0.454 (95% CI: 0.098–2.11), 1.370 (95% CI: 0.516–3.637), and 2.575 (95% CI: 0.978–6.785), respectively, with no significant differences detected between the groups. Conclusion This meta‐analysis shows that dexmedetomidine is a safe and effective sedative agent for gastrointestinal endoscopy, especially endoscopic retrograde cholangiopancreatography and endoscopic submucosal dissection.